2019
DOI: 10.1186/s13059-019-1923-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial genomes from non-human primate gut metagenomes expand the primate-associated bacterial tree of life with over 1000 novel species

Abstract: BackgroundHumans have coevolved with microbial communities to establish a mutually advantageous relationship that is still poorly characterized and can provide a better understanding of the human microbiome. Comparative metagenomic analysis of human and non-human primate (NHP) microbiomes offers a promising approach to study this symbiosis. Very few microbial species have been characterized in NHP microbiomes due to their poor representation in the available cataloged microbial diversity, thus limiting the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 98 publications
4
76
0
Order By: Relevance
“…Consistent with studies on NHPs (35)(36)(37) and humans (4, 5, 7), we also found the gut microbiome was dominated by Bacteroidetes and Firmicutes phyla across the age groups. Similar to a study by Biagi et al (4), we found an overall increase in opportunistic pathobionts such as Proteobacteria phylum, and changes in Bacteroidetes and Firmicutes in old monkeys.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with studies on NHPs (35)(36)(37) and humans (4, 5, 7), we also found the gut microbiome was dominated by Bacteroidetes and Firmicutes phyla across the age groups. Similar to a study by Biagi et al (4), we found an overall increase in opportunistic pathobionts such as Proteobacteria phylum, and changes in Bacteroidetes and Firmicutes in old monkeys.…”
Section: Discussionsupporting
confidence: 91%
“…Human (7,8,40) and NHP (35,37) studies reported prevalence of genera that belong to Prevotellaceae in the gut. Interestingly, members of Prevotellaceae and Helicobacteraceae are known to augment mucosal inflammation enabling dissemination of bacterial products to the systemic circulation (36,37,41). We previously demonstrated associations between increased systemic microbial translocation and innate immune responses impacting metabolic health in aged monkeys (12).…”
Section: Discussionmentioning
confidence: 95%
“…New technologies and computational tools are generating an unprecedented amount of strain-specific genomic information that can be the foundation of a new generation of microbiome studies [2,12,13,34,35]. Large-scale species-specific whole-genome investigations can now be performed without cultivation [14] and-using metagenomic assembly combined with a reference-dependent binning approach-can be applied on many thousands of single metagenomes.…”
Section: Discussionmentioning
confidence: 99%
“…In order to find E. rectale genomes assembled from wild non-human primate metagenomes, we assembled and binned as described elsewhere [2,51] a total of 2895 metagenomic high-quality genomes obtained from 175 publicly available metagenomes from wild, nonhuman primates (Additional file 8: Table S7). These 175 metagenomes come from four different datasets spanning 22 non-human primate species including chimpanzees and gorillas from 14 different countries on five continents [45][46][47][48].…”
Section: Based On Metagenomic Assembly and Binningmentioning
confidence: 99%
“…We used PhyloPhlAn 3.0 to generate the phylogenies of 1000 S. aureus reference genomes and 135 S. aureus isolates as discussed in the results. To evaluate the phylogeny generated by Phy-loPhlAn 3.0 we used the tqDist 71 function available in the R quartet package to compare quartet distances between the PhyloPhlAn 3.0 and the manually curated reference phylogeny 72 .…”
Section: Methodsmentioning
confidence: 99%